2016
DOI: 10.1016/j.kint.2016.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Multiphasic effects of blood pressure on survival in hemodialysis patients

Abstract: Dialysis patients exhibit an inverse, L- or U-shaped association between blood pressure and mortality risk, in contrast to the linear association in the general population. We prospectively studied 9333 hemodialysis patients in France, aiming to analyze associations between predialysis systolic, diastolic, and pulse pressure with all-cause mortality, cardiovascular mortality, and nonfatal cardiovascular endpoints for a median follow-up of 548 days. Blood pressure components were tested against outcomes in time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 36 publications
3
47
1
2
Order By: Relevance
“…This finding is also clinically significant for dialysis patients because predialysis systolic hypertension remains a significant predictor of all‐cause death and cardiovascular survival . However, given the “U” curve association between BP and mortality in haemodialysis patients, greater reductions in SBP are not necessarily better . In our study, we selected the patients who had an average predialysis BP higher than 140/90 mmHg following the recommendations of the 2005 National Kidney Foundation Kidney Disease Outcomes Quality Initiative (KDOQI) clinical practice guideline.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding is also clinically significant for dialysis patients because predialysis systolic hypertension remains a significant predictor of all‐cause death and cardiovascular survival . However, given the “U” curve association between BP and mortality in haemodialysis patients, greater reductions in SBP are not necessarily better . In our study, we selected the patients who had an average predialysis BP higher than 140/90 mmHg following the recommendations of the 2005 National Kidney Foundation Kidney Disease Outcomes Quality Initiative (KDOQI) clinical practice guideline.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we selected the patients who had an average predialysis BP higher than 140/90 mmHg following the recommendations of the 2005 National Kidney Foundation Kidney Disease Outcomes Quality Initiative (KDOQI) clinical practice guideline. However, recent data from the Dialysis Outcome and Practice Pattern Study (DOPPS) and Hannedouche et al have shown that the optimal predialysis SBP is in the range of 130–159 or 165 mmHg . But in any case, lowering BP is not the objective of hypertension management; the ultimate goal of BP control is to reduce hypertension related‐cardiovascular and cerebrovascular events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prospectively collected predialysis systolic BP among 9333 hemodialysis patients in France using BP as a time-varying covariate also found a U-shaped association between systolic BP and mortality, with a systolic BP of 165 mm Hg associated with the lowest risk. 10 This seemingly paradoxical observation has been labeled "reverse epidemiology," in that the relationship between BP and outcomes is the reverse of what has been illustrated in the general population.…”
Section: Relationship Of Bp With Mortalitymentioning
confidence: 99%